## Trending News

Promoted

# How would you solve this? Step by step?

(2gh^4)^3 [(-2g^4h)^3]^2

### 2 Answers

Relevance

- StevenLv 78 years agoFavorite Answer
(2gh^4)^3 [(-2g^4h)^3]^2you have a parenthesis

times a bracket

that has a parenthesis inside the bracket

perform the parenthesis inside the bracket 1st

(-2g^4h)^3

-2^3= -8

when you raise an exponent exponentially, you multiply

multiply by 3

-8g^12h^3

now the bracket

[-8g^12h^3]^2

-8^2=64

again, multiply the exponents by 2

64g^24h^6

now perform the other parenthesis

2^3=8

multiply the exponents by 3

8g^3h^12

now multiply the parenthesis and the bracket

when you multiply exponents, you add

(8g^3h^12)^3[64g^24h^6]

8*64=512

512g^5h^18

- 8 years ago
(2g h^4)^3 [(-2g^4 h)^3]^2 =

2^3 g^3 h^12 [( -2^3 g^12 h^3)^2] =

2^3 g^3 h^12 [ -2^6 g^24 h^6] =

2^9 g^27 h^20

Still have questions? Get your answers by asking now.